Economic transformation in Africa from the bottom up: New evidence from Tanzania - Diao, Xinshen; Kweka, Josaphat; McMillan, Margaret S.; Qureshi, Zara (World Bank, 2020)
Tanzania's rapid labor productivity growth has been accompanied by a proliferation of small, largely informal firms. Using Tanzania's first nationally representative survey of micro, small, and medium-sized enterprises (MSMEs)—this paper explores the nature of these businesses. It finds that these firms are located in both rural and urban areas and that they operate primarily in trade services and manufacturing. Roughly half of all business owners say they would not leave their job for a full-time salaried position. Fifteen percent of these small businesses contribute significantly to economy-wide labor productivity. The most important policy implication of the evidence presented in this paper is that if the goal is to grow MSMEs with the potential to contribute to productive employment, policies must be targeted at the most promising firms.